Labour taxation and its impact on economic growth: Complex analysis - Rudolf Macek (DANUBE: Law, Economics and Social Issues Review, 2018)
The aim of the article is to provide a complex analysis of labour taxation impact on economic growth in OECD countries. As main approximators of taxation, implicit tax rates and the World Tax Index are used. Methods and tests of dynamic panel regression with the Arellano-Bond estimator are used from the methodological point of view. From the results of complex analysis, it is evident that there exists a non-linear relationship between tax revenues (implicit tax rates, world tax index) and tax burden (tax rates). There also exists a negative relationship between labour taxation and economic growth and the impact of labour taxation is the most harmful for economic growth. Therefore, in an effort to stimulate economic growth, labour taxation expressed by personal income taxes and social security contributions should be reduced.
Keywords: 330; Labour Taxation; Implicit Tax Rates; World Tax Index; Laffer Curve; Economic Growth; Dynamic Panel Regression